Measuring Health: Wearables in Fitness Tracking, Stress Relief, and Sleep Management - Julia Sieniawska; Patrycja Proszowska; Magda Madoń; Zuzanna Kotowicz; Adrianna Orzeł; Aleksandra Pich-Czekierda; Daria Sieniawska (Kazimierz Wielki University, 2024)
Introduction In today's fast-paced world, the quest for better health has led to the rise of wearable devices. These innovative tools, from smartwatches to activity trackers, offer real-time insights into our physical activity, stress levels, and sleep patterns. By seamlessly integrating into our daily lives, wearables empower individuals to take control of their health and well-being like never before. Aim of the study The present review aims to provide the readers with a broader knowledge of the impact of wearables on health. Materials and methods This article provides a foundation for understanding the significance and potential of wearable devices in promoting health and wellness. Comprehensive literature searches were performed across the main electronic databases of PubMed and Google Scholar for studies published in the English language about use and validation of wearables. Results Wearable devices are effective tools in promoting physical activity, managing stress, and monitoring sleep. With advanced sensors and algorithms, these devices enable users to track their health progress in real-time and provide personalized strategies for improvement. By combining fitness tracking, communication, and stress management capabilities, these devices possess the capacity to empower individuals in maintaining a healthy lifestyle and have become a potential option at the point where technology and personal health meet. As a result, wearable devices have tremendous potential to transform healthcare and enhance quality of life.